Comparison of Rockall and Glasgow-Blatchford Scores in GI Bleeding - Boğa, Erkan (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: This study aimed to compare the clinical effectiveness of the Rockall score and the Glasgow-Blatchford Score (GBS) in patients presenting to the emergency department with suspected gastrointestinal bleeding. Methods: A retrospective cross-sectional study was conducted on 350 patients admitted to Esenyurt Necmi Kadıoğlu State Hospital between January 1, 2023, and December 31, 2024, with complete clinical data. The study evaluated the predictive performance of both scoring systems regarding 30-day mortality, rebleeding, need for blood transfusion, and intensive care unit (ICU) admission. Results: The GBS demonstrated superior performance over the Rockall score in early risk assessment and in guiding hospital admission or discharge decisions. Conversely, the Rockall score was more effective in predicting long-term prognosis and the risk of rebleeding. According to ROC analysis, GBS (AUC: 0.83) outperformed the Rockall score (AUC: 0.78) in predicting mortality. Subgroup analysis indicated that the predictive value of the Rockall score declined in patients on anticoagulant therapy, while both scores showed increased predictive accuracy in patients aged ≥65 years. Conclusion: The findings suggest that the GBS is more suitable for early clinical decision-making in the emergency setting, whereas the Rockall score should be considered for long-term risk evaluation in patients with gastrointestinal bleeding.